2000
DOI: 10.1210/mend.14.8.0498
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of EGF Family of Growth Factors and COX-2 in the Uterus during the Preattachment and Attachment Reactions of the Blastocyst with the Luminal Epithelium Correlates with Implantation Failure in LIF- Deficient Mice

Abstract: Various mediators, including cytokines, growth factors, homeotic gene products, and prostaglandins (PGs), participate in the implantation process in an autocrine, paracrine, or juxtacrine manner. However, interactions among these factors that result in successful implantation are not clearly understood. Leukemia inhibitory factor (LIF), a pleiotropic cytokine, was shown to be expressed in uterine glands on day 4 morning before implantation and is critical to this process in mice. However, the mechanism by whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(94 citation statements)
references
References 63 publications
3
91
0
Order By: Relevance
“…9), supporting the view that reduced preimplantation P 4 secretion from the loss of HB-EGF doest not disrupt P 4 's role in uterine receptivity. Because estrogen is also critical for uterine receptivity, we examined the effect of reduced preimplantation E 2 secretion on uterine expression of leukemia inhibitory factor (LIF), an E 2 -target gene (34), and found that Lif was expressed in uterine glands in both WT and Hbegf Ϫ/Ϫ females on day 4 morning (SI Fig. 9).…”
Section: Attenuated Preimplantation Ovarian Estrogen Secretion In Hbementioning
confidence: 99%
“…9), supporting the view that reduced preimplantation P 4 secretion from the loss of HB-EGF doest not disrupt P 4 's role in uterine receptivity. Because estrogen is also critical for uterine receptivity, we examined the effect of reduced preimplantation E 2 secretion on uterine expression of leukemia inhibitory factor (LIF), an E 2 -target gene (34), and found that Lif was expressed in uterine glands in both WT and Hbegf Ϫ/Ϫ females on day 4 morning (SI Fig. 9).…”
Section: Attenuated Preimplantation Ovarian Estrogen Secretion In Hbementioning
confidence: 99%
“…Based on in situ analyses, Lif exhibits a biphasic expression pattern in the mouse uterus on D4 of pregnancy. In the morning it is expressed in the glandular epithelium and in the evening it is expressed in stromal cells at the site of embryo attachment (Song et al 2000, Song & Lim 2006. These observations suggest that on D4, LIF has two roles: first, in the preparation of the uterus, and second, in the attachment of the embryo to the endometrial lining.…”
Section: Kisspeptin Positively Regulates Embryo Implantationmentioning
confidence: 88%
“…This is based on the observations that the expression of uterine Lif is upregulated at ovulation and that Lif is not expressed in the uterus during experimentally induced delayed implantation but is rapidly induced following an injection of estrogen (Bhatt et al 1991, Song et al 2000. Using an RNase protection assay, Chen et al (2000) confirmed that estrogen rapidly upregulates uterine Lif expression and further demonstrated that LIF can replace nidatory estrogen at inducing both implantation and decidualization in ovariectomized mice.…”
Section: Kiss1mentioning
confidence: 99%
“…LIF acts on the uterine epithelium in an autocrine/paracrine manner, and in vitro LIF stimulates proliferation of stromal fibroblasts (Salamonsen et al 1997). The uterine effect of LIF seems to be mediated via Hbegf since Lif-/-mice show deficient expression of Hbegf (Song et al 2000). Thus, the cell cycle regulatory signalling pathways involved in decidualization are under the commands of Hbegf, Hoxa10 and Lifr.…”
Section: Discussionmentioning
confidence: 99%